Research of influence of loading on efficiency of greasing of oils in contact - Туриця, Ю.О. (Problems of Tribology, 2014)
In work laws of change are investigated of change of hydrodynamic and not hydrodynamic components of a thickness of a lubricant layer in contact depending on loading are investigated. It is established that the increase in contact loading accelerates adsorption processes on the activated surfaces of a friction, owing to formation on them boundary adsorption layers raises, and stability of formation of a bearing hydrodynamic lubricant layer depending on pressure speaks increase in a firm phase threw on viscosity of oil in contact.